5(y-3)=-1(y+6)

Simple and best practice solution for 5(y-3)=-1(y+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y-3)=-1(y+6) equation:


Simplifying
5(y + -3) = -1(y + 6)

Reorder the terms:
5(-3 + y) = -1(y + 6)
(-3 * 5 + y * 5) = -1(y + 6)
(-15 + 5y) = -1(y + 6)

Reorder the terms:
-15 + 5y = -1(6 + y)
-15 + 5y = (6 * -1 + y * -1)
-15 + 5y = (-6 + -1y)

Solving
-15 + 5y = -6 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
-15 + 5y + y = -6 + -1y + y

Combine like terms: 5y + y = 6y
-15 + 6y = -6 + -1y + y

Combine like terms: -1y + y = 0
-15 + 6y = -6 + 0
-15 + 6y = -6

Add '15' to each side of the equation.
-15 + 15 + 6y = -6 + 15

Combine like terms: -15 + 15 = 0
0 + 6y = -6 + 15
6y = -6 + 15

Combine like terms: -6 + 15 = 9
6y = 9

Divide each side by '6'.
y = 1.5

Simplifying
y = 1.5

See similar equations:

| -10n+3(8+8n)=-6n(n-4) | | 4(1-5x)-5x(7x-2)= | | 125=-4(2+3x)-7x | | 250-Q^2=4Q | | 8(w+8)-(2+6w)=w | | 1/138(11x+9x)-13=19/345x | | 390/(5(7+6)) | | 1/3-19/(4x)=1/4-1/6x | | 7x+8-3=12 | | 3(2x-1)+(3/2)(3x+4)=1-4x | | 6/(x+7)=8/x | | 3x^2-8=40 | | -3+8=27 | | 0.03(x-6)+0.02(x-4)=5.24 | | 10n+3(8+8n)=6n(n-4) | | 2x+x-3=45 | | X-1=-1+3x | | 19+5-8*4/2= | | 2x^4+11x^2+15=o | | 6/x+7=8/x | | 8-7k+3=-10 | | -1(4x-5)=x | | 2(x-8)+7=5(x+2)-3x-1 | | 4f+g=-2f-14 | | (x^2-2x-8)/(x^3+x^2-2x) | | 2.5y+7.5y=4.2 | | 4f+h=-2g-14 | | B-38=-79 | | x^2+2x-1= | | 7(6x-1)+6(-6x+8)= | | 6[4(2x-1)]=80-8 | | 5(-7+x)=5 |

Equations solver categories